2008
DOI: 10.1021/jo8000595
|View full text |Cite
|
Sign up to set email alerts
|

Facile Assembly of Fused Benzo[4,5]furo Heterocycles

Abstract: A concise synthesis of fused benzo[4,5]furo heterocycles 18 has been developed. Chemo/regioselective Suzuki coupling between 1,2-dihaloarene 17 and alpha-hydroxyphenylboronic acid or ester 20 gives biaryl phenol 19, which then undergoes copper(I) thiophene-2-carboxylate (CuTC)-mediated intramolecular cyclization to afford 18 in good overall yield. This method has broad substrate scope and allows facile assembly of a wide variety of benzo[4,5]furo heterocycles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(45 citation statements)
references
References 14 publications
0
45
0
Order By: Relevance
“…Treatment of 4 with an excess amount of ethyl triflate furnished ammonium salt 5, which was subsequently transformed into the acetylated product 6. Demethylation of 6 followed by the formation of benzofuran structure via intramolecular Ullmann condensation 22 provided the target compound, BINDY.…”
Section: Synthesis Of Bindymentioning
confidence: 99%
“…Treatment of 4 with an excess amount of ethyl triflate furnished ammonium salt 5, which was subsequently transformed into the acetylated product 6. Demethylation of 6 followed by the formation of benzofuran structure via intramolecular Ullmann condensation 22 provided the target compound, BINDY.…”
Section: Synthesis Of Bindymentioning
confidence: 99%
“…In 2008, the Suzuki–Miyaura monoarylation of 2,4,5,6‐tetrachloropyrimidine ( 480 ) was investigated by Yang et al 172…”
Section: Cross‐coupling Reactions Of Polyhalogenated Six‐membered Hmentioning
confidence: 99%
“…Worthy of note is that the first and only example of a selective Suzuki–Miyaura monoarylation of a dihalogenated quinoxaline was described in 2008 by Liu et al.,172 who found that the Pd(OAc) 2 /PPh 3 ‐catalyzed reaction between 1.5 equiv. of 2,3‐dichloroquinoxalime ( 492 ) and 5‐fluoro‐2‐methoxyphenylboronic acid ( 493 ) in a 4:1 mixture of MeCN and water at 60 °C in the presence of 3.0 equiv.…”
Section: Cross‐coupling Reactions Of Polyhalogenated Six‐membered Hmentioning
confidence: 99%
“…Liu and co-workers [47] developed a concise synthesis of fused benzo [4,5]furo heterocycles 169 that are a common structural motif in biologically active compounds and drug candidates (Scheme 32). One of the key reactions is a chemo/regioselective Suzuki coupling.…”
Section: Synthesis Of Oxygen-bearing Heterocyclic Compoundsmentioning
confidence: 99%